Modeling of Six Pulse Voltage Source Inverter based STATCOM with PWM and Conventional Triggering - Sachin Sharma; Alok Pandey; Nitin Kumar Saxena (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
In the present study, a six pulse inverter is triggered using conventional sequential and pulse width modulation (PWM) technique simultaneously for comparing their results. FACTS devices such as STATCOM are the most emerging areas in today’s power system. This STATCOM is a power electronic based converter circuit in which inverter circuit is fabricated for the purpose of voltage control and reactive power compensation through its current flow. A six pulse inverter is developed that can be generalized for developing any number of multiple of six pulse inverters by cascading them in parallel using transformers connection. Voltage source Inverter (VSI) is the most commonly used inverter that can be modeled for electrical system based studies. A methodology is presented to trigger the STATCOM inverter circuit using conventional and PWM techniques, and then the results are compared using MATLAB Simulink model